Disturbance Suppression Ability Evaluation for Delayed Load Frequency Control Participated With EV Aggregators and Redox Flow Batteries - Wang, Hong-Zhang; Shangguan, Xing-Chen; Zhang, Chuan-Ke; Wei, Chen-Guang; Yuan, Zhe-Li; He, Yong (IEEE transactions on industrial informatics, 2025)
The storage sources in auxiliary frequency regulation service (AFRS) for load frequency control (LFC) have a fast response time and are effective in smoothing wind power output. In this article, the disturbance suppression ability for delayed LFC is evaluated considering the participation of electric vehicle (EV) aggregators and redox flow batteries (RFBs)-based AFRS. First, a model for the delayed LFC with wind power is constructed, incorporating the EV aggregator and RFB participation. A criterion for evaluating the disturbance suppression ability of delayed LFC is presented, incorporating more system information to reduce conservativeness compared to existing methods. Finally, case studies show that the introduction of RFBs improves the disturbance suppression ability and the delay tolerance ability of LFC. Simulation and experimental tests demonstrate that the theoretical improvement produces more accurate evaluation results.